Pemilihan Peserta Olimpiade Bahasa Inggris Menggunakan Metode Hybrid ROC-EDAS (SMP Muhammadiyah 58) - Dewi Yulistiana (STMIK Budi Darma, 2022)
The English Olympiad is one of the prestigious events in the field of education where the winners of the competition are talented and selected people with above average abilities, the winners of the English Olympiad competition also affect the good name of the educational institution where the contestants receive education . This makes it important to select participants who will be sent to take part in competitions that have been held so as to minimize the possibility of unwanted things happening. The election is carried out using the help of a decision support system to help make it easier to select and select candidates subjectively and accurately. This research will look at the work of the Hybrid ROC-EDAS method in helping the selection of Olympic participants more accurately.